Neural basis of disgust perception in racial prejudice. Issue 12 (29th September 2015) - Liu, Yunzhe; Lin, Wanjun; Xu, Pengfei; Zhang, Dandan; Luo, Yuejia
Abstract: Worldwide racial prejudice is originated from in‐group/out‐group discrimination. This prejudice can bias face perception at the very beginning of social interaction. However, little is known about the neurocognitive mechanism underlying the influence of racial prejudice on facial emotion perception. Here, we examined the neural basis of disgust perception in racial prejudice using a passive viewing task and functional magnetic resonance imaging. We found that compared with the disgusted faces of in‐groups, the disgusted faces of out‐groups result in increased amygdala and insular engagement, positive coupling of the insula with amygdala‐based emotional system, and negative coupling of the insula with anterior cingulate cortex (ACC)‐based regulatory system. Furthermore, machine‐learning algorithms revealed that the level of implicit racial prejudice could be predicted by functional couplings of the insula with both the amygdala and the ACC, which suggests that the insula is largely involved in racially biased disgust perception through two distinct neural circuits. In addition, individual difference in disgust sensitivity was found to be predictive of implicit racial prejudice. Taken together, our results suggest a crucial role of insula‐centered circuits for disgust perception in racial prejudice. Hum Brain Mapp 36:5275–5286, 2015 . © 2015 Wiley Periodicals, Inc.